2008
DOI: 10.1590/s1516-44462008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole in the treatment of posttraumatic stress disorder: an open-label trial

Abstract: Objective: Post traumatic stress disorder is frequent in the general population (F = 11.247, p = 0.001); (F = 8.931, p = 0.011); (F = 8.633, p = 0.012); (F = 10.127 p = 0.007); (F = 1.580, p = 0.042 7 (± 23,1) e 51,4 (± 31,4) (F = 11,247, p = 0,001);7 (± 13,4) e 25,4 (± 18,2) (F = 8,931, p = 0,011);4 (± 0,45) e 2,27 (± 0,57) (F = 8,633, p = 0,012);6 (± 14,11) e 94,01 (± 25,06) (F = 10,127 p = 0,007);06 (± 11,6) e 21,35 (± 12,6) (F = 1,580, p = 0,042

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In its limited use at the VAMC, aripiprazole had three failures and one partial response within a dosing range of 5.0–10.0 mg. A chart review of 27 treatment resistant veterans with military-related PTSD [99] and a 16-week open-label trial of aripiprazole 9.6 ± 4.3 mg/day with 32 civilians with PTSD recorded reduction of symptoms [100]. The aripiprazole dosing range in the latter study was relatively similar to that utilized by the VAMC clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In its limited use at the VAMC, aripiprazole had three failures and one partial response within a dosing range of 5.0–10.0 mg. A chart review of 27 treatment resistant veterans with military-related PTSD [99] and a 16-week open-label trial of aripiprazole 9.6 ± 4.3 mg/day with 32 civilians with PTSD recorded reduction of symptoms [100]. The aripiprazole dosing range in the latter study was relatively similar to that utilized by the VAMC clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical antipsychotics: Some data suggest that the atypical antipsychotics, risperidone (Level 2) [1030], aripiprazole (Level 3) [1031,1032], and quetiapine (Level 3) [1034,1035] may be a useful alternative to SSRIs for some patients with PTSD. A meta-analysis of seven RCTs using atypical antipsychotics, either as monotherapy or adjunctively, concluded that these agents may be beneficial in the treatment of PTSD, particularly for the symptom of “intrusion” [1061].…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Two small RCTs of aripiprazole have been conducted in OCD with promising preliminary results (56, 57). In addition, open label trials of aripiprazole have been conducted in GAD, panic disorder (58), MDD with anxious features (59) and PTSD (60) with initial encouraging results. Additional randomized controlled data are required to further characterize the efficacy of aripirazole in anxiety disorders.…”
Section: Competitive Environmentmentioning
confidence: 99%